Seva in Mata Amritanandamayi Mission: Social Service as a Public Face of Faith - Pandya, Samta P. (Implicit religion, 2016)
Based on fieldwork with Mata Amritanandamayi Mission (MAM) headed by Mata Amritanandamayi and headquartered in Kollam, Kerala, India, I discuss its aspects of seva or social service. I propose that seva in MAM is done by followers and disciples volitionally and then it becomes a doctrine in Amma's ministry. I observed two social service projects in terms of their interfaces with various systems such as economic-political-social, partnerships and nature of routine operations. I make some propositions on seva in MAM and emphasize that it typifies the living guru's expansive agency, uncontainability and more specifically a form of implicit religion. For followers, seva is a means to gain a place in Amma's coterie, and, the actual operations of the projects signify a sacred-secular partnership such that we can begin to speak of its politics.